Upaya Meningkat Kan Pemahaman Siswa Melalui Metode Debat Aktif Pada Mata Pelajaran Fiqih Siswa Kelas VII MTs Teladan Gebang - Rahma Fadillah Br Simatupang, Usmaidar, Ahmad Fuadi (Pusdikra Publishing, 2023)
The purpose of this study is to find out how to improve students' understanding of the subject of Fiqh Class VII MTs Teladan Gebang. To find out the learning of fiqh using the active debate method increases the understanding of class VII students at MTs Teladan Gebang. To find out the results of studying jurisprudence after using the Active Debate method for class VII MTs Teladan Gebang. The model in this study uses the Kurt Lewin research model which consists of 4 stages namely; planning, implementation of action, observation and reflection. The subjects of this study were class VII MTs Teladan Gebang using the recitation learning method. Consisting of 35 students,. Data collection techniques using interviews, observation, documentation, and written test assessment The research results of the active debate method can increase the ability to describe material through the active debate method. The student material descriptions increased after the active debate method was applied. Based on the results of observations, student learning activities in cycle II increased compared to cycle I. The average observation cycle I was 80%, the average cycle II was 87.17%. . In cycle II there was an increase in the percentage of student learning activity by 10.% from cycle I. Meanwhile, the learning outcomes for elaborating material also experienced an increase. student learning outcomes for analyzing material obtained an average of 67. In cycle II the average learning outcomes increased, the first meeting of student learning outcomes for analyzing material obtained an average value of 71.34 and the second meeting of student learning outcomes for analyzing material obtained average 87.00. From the results of the pretest before the action obtained an average value of 66.14 and the results of the posttest after the action obtained an average value of 75.83. If measured by N-gain, the average student ability is 0.29 in the medium category. This shows that the active debate method according to MTs Teladan Gebang Many students is considered good, namely between the classification of 76-100%. Thus the application of the active debate method can improve students' material description skills.